If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2b+7)-5=2(5b+4)+2b
We move all terms to the left:
3(2b+7)-5-(2(5b+4)+2b)=0
We multiply parentheses
6b-(2(5b+4)+2b)+21-5=0
We calculate terms in parentheses: -(2(5b+4)+2b), so:We add all the numbers together, and all the variables
2(5b+4)+2b
We add all the numbers together, and all the variables
2b+2(5b+4)
We multiply parentheses
2b+10b+8
We add all the numbers together, and all the variables
12b+8
Back to the equation:
-(12b+8)
6b-(12b+8)+16=0
We get rid of parentheses
6b-12b-8+16=0
We add all the numbers together, and all the variables
-6b+8=0
We move all terms containing b to the left, all other terms to the right
-6b=-8
b=-8/-6
b=1+1/3
| x-1)+(5x+3)+(5x+3)=180 | | 7/9+p=25/27 | | -142=-3b-5(8b-6) | | 1/2+x=200 | | 6x+7/4=5x | | x2+2x=5x | | k=−52 | | 25=m-15= | | 137^2=105^2+b^2 | | -8=5p-4p | | 0=-8(2n-4)+5 | | 5x-6=16+x | | .75(8b+4)-1=4b=14 | | 3x+7/4=2x | | 6x=36-x | | 2(a+4)-7=1/2(5+2a) | | 4x-2=43-5x | | -8=2-3a-7a | | -89=7n-3(3-3n) | | x-9.9=44 | | x.2/5=0.6 | | 0=-7n+4(-6+3n) | | 66=z-11 | | 5(3x+9)=-38+23 | | 8^(x+1)=25 | | 3=a+4+6 | | 1+2p+5=-2 | | 5x+11=3x+63 | | 88+c=500 | | 5x-(-12x+20)=-3 | | -5/6=u+6 | | 3x-6=6x=3 |